HUBUNGAN ANTARA MOTIVASI KERJA GURU DAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN DISIPLIN KERJA GURU - Agus Wagito (UNIVERSITAS BENGKULU, 2016)
The aim of the research is to find out the correlation between teacher’s working motivation and principal’s leadership with teacher’s working discipline. The applied research method was survey method with correlation approach and data analysis techniques using both linier and multiple correlation and regression statistic test. The results show that teacher’s wor ki n g discipline at public senior high school number 1 Ketahun North Bengkulu wascorrelated with teacher’s working motivation and principal’s leadership.Keywords: teacher, motivation, principal and discipline